MANFAAT WORKSHOP PENELITIAN TINDAKAN KELAS DAN PENULISAN KARYA ILMIAH BAGI KELOMPOK KERJA GURU GUGUS SEKOLAH SATRIYO UTOMO KECAMATAN NGAWEN BLORA TAHUN 2010 - Nur Khoiri; Ngurah Ayu N. M.; Didik Ariyanto; Rinawati Ariesta (Universitas PGRI Semarang, 2011)
Abstract This report describes how physic teachers?óÔé¼Ôäó competency can be strengthening by exploring their writing capability through a workshop conducted by team of community service. This training was given to KKG / teachers?óÔé¼Ôäó group of Satriyo Utomo Ngawen Blora in 2010. The materials are how to find the topic, how to write a proposal of classroom research, and how to arrange a report of classroom action research, then how to make it into an article. By having these skills, it is expected that they will be able to arrange their own action research and article in order to raise their grade and prosperity. Team also gives them a full advice for those who want to make a proposal, a report and an article until they enable make their own classroom research by themselves. Through this training, KKG Satriyo Utomo Ngawen feels that it is really needed to sharpen and empower their writing skill especially writing a classroom action research and an article. Key words : teachers?óÔé¼Ôäó competency, a classroom action research, an article.